2017
DOI: 10.1016/j.jinf.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Three year evaluation of Xpert MTB/RIF in a low prevalence tuberculosis setting: A Scottish perspective

Abstract: Xpert MTB/RIF was rapid and accurate in diagnosing pulmonary TB in a low prevalence area. Rapid results will influence infection prevention and control and treatment measures. The excellent NPV obtained suggests further work should be carried out to assess its role in replacing microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…In the study of Parcell B.J. et al ( 2017), with increasing the degree of smear (+1, +2, +3 or +4), the frequency of consolidation increased significantly( in degrees +1, +2, +3, the frequency of consolidation was +4 81%, 95%, 100% respectively) [14]. In the study of Brahmapurkar K.P.…”
Section: Discussionmentioning
confidence: 95%
“…In the study of Parcell B.J. et al ( 2017), with increasing the degree of smear (+1, +2, +3 or +4), the frequency of consolidation increased significantly( in degrees +1, +2, +3, the frequency of consolidation was +4 81%, 95%, 100% respectively) [14]. In the study of Brahmapurkar K.P.…”
Section: Discussionmentioning
confidence: 95%
“…Akciğer örnekleri için GX testinin duyarlılığı %82.7, özgüllüğü %98.7 bulundu. Aralarında meta-analizlerin de bulunduğu dünyada yapılan çeşitli çalışmalarda, akciğer örneklerinde GX testinin duyarlılığı %58-100, özgüllüğü %86-100 arasında geniş bir yelpazede dağılmaktadır (5,16,19,20) . (20) ile Parcell ve ark.…”
Section: Mgit Sire Yöntemiunclassified
“…(20) ile Parcell ve ark. (19) tarafından yapılan çalışmalara göre düşük olduğu gözlenmektedir. Çalışmamızda kültürde MTK üremesi saptanıp GX testi ile MTK DNA'sı saptanmayan balgam örneklerinin tümü ARB negatif örneklerdi.…”
Section: Mgit Sire Yöntemiunclassified
See 1 more Smart Citation
“…Luetkemyer et al and Parcell et al [ 56 , 57 ] showed in their studies that the performance of Xpert MTB/RIF did not differ between higher- and low-prevalence areas. For HIV-associated TB, Xpert MTB/RIF has lower sensitivity [ 44 ].…”
Section: Introductionmentioning
confidence: 99%